Pemberdayaan Kader dalam Pembentukan Pos Pembinaan Terpadu (Posbindu) Penyakit Tidak Menular di Ngandong Sleman Yogyakarta: Empowerment of Cadres in the Establishment of Posbindu Non-Communicable Diseases in Ngandong Sleman Yogyakarta - Erlina Marfianti; Sunarto Sunarto; Dimas Adhi Pradana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The prevalence of non-communicable diseases (NCD) in Indonesia is currently increasing. Data from WHO states that 71% of the causes of death worldwide are NCD. Control of risk factors and early detection of non-communicable diseases (NCD) are the keys to reducing the number of cases and mortality of NCD. Posbindu is a preventive, promotive effort that involves community participation. The ability of cadres and community awareness are not the same in every area. In this regard, our community service activities aim to optimize cadres in controlling NCD through the establishment and implementation of Posbindu. This program consists of 5 actions: Training of cadres about Posbindu, Counseling, and education to cadres and the community about non-communicable diseases, especially hypertension and diabetes mellitus, Procurement and training on the use of medical devices for Posbindu, Creation of information and communication media for health education to the public, and Establishment of Posbindu and its implementation. The results of this program are increasing the understanding of cadres about Posbindu, increasing the knowledge of cadres and the community about NCD, and the formation of Posbindu, which has been implemented in the community. Active participation of the cadres and the community is expected to ensure the continuity of this activity.